Effect of screen reading and reading from printed out material on student success and permanency in introduction to computer lesson - Tuncer, Murat; Bahadır, Ferdi (My University, 2014)
In this study, the effect of screen reading and reading from printed out material on student success and permanency in Introduction to Computer Lesson is investigated. Study group of the research consists of 78 freshman students registered in Erzincan University Refahiye Vocational School Post Service department. Study groups of research consist of an experiment group and a control group. With a random selection 38 students were assigned as experiment group and 40 students were assigned as control group. In this manner, experiment group with 38 students used screen reading, and control group with 40 students used printed out material for education. Study was designed as control group model with pretest and posttest. Both experiment and control groups were applied pretest and posttest within the research. In process of data analysing, ancova and multiple variance analysis were used. It was found on success tests that there is not a significant difference between posttests corrected according to pretests of control and experiment groups. But, a significant difference between Access and permanency tests in favour of control group was found. Furthermore, dual effect of applied method and gender on posttest success scores and delayed test scores was found to be insignificant. Results of the studies show that reading from printed out material is more efficient than screen reading.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Screen reading; Reading from printed out material; Student success; Introduction to computer lesson